KAJIAN GIZI MIKRO SENG (Zn) PADA KEJADIAN FILARIASIS (STUDI KASUS DI KOTA PEKALONGAN) - Dewi Nugraheni Restu Mastuti (Universitas Pekalongan, 2015)
Microfilariae infection in the human body does not always cause symptoms. Individuals infected with filaria would induce a Th2 response by increasing the production of IL-4, IL-5, IL-13 and increased serum levels of IgE. Zinc deficiency is directly related to the regulation of the immune response are reduced due to decline in lymphopoesis as well as the effect on the immune response and the production of antibodies in people with normal nutritional status. This research will analyze the relationship between zinc intake and zinc status with the incidence of filariasis.Methods: The study using observative analytic case control approach. Samples were selected 30 cases and 30 controls. Zinc intake assessment done by using foodfrequency (FFQ) and food recall 3 x 24 hours and then treated with Nutrisoft program. Assessment of serum zinc is done by taking samples of venous blood as much as 3 cc made 1 times. Statistical analysis was performed with the Fisher exact test SPSS 16.0.Results: A total of 29 cases (96%) experienced a lack of zinc intake (p value = 0.103), and a total of 24 controls (80%) experienced a lack of zinc intake. Zinc status were not significantly different in the case and control groups (p = 1.000).Conclusions: The intake of zinc and zinc status were not associated with a lower incidence of filariasisSuggesstion: People are expected to consume the food should be varied so that the nutritional needs both macro and micro will be fulfilled Keywords: filariasis, Zinc Intake, Serum Zinc, Immunity